Solitary vascular malformation of the clitoris - Haritharan, T; Ab Rashid, Islah Munjih; Zulfiqar, A; Thambi Dorai, C R (Malaysian Medical Associations, 2006)
Isolated involvement of the clitoris by vascular malformation (VM) is very rare. Clinically, the lesion simulates female pseudohermaphroditism. A five-year old girl presented with clitoromegaly and a clinical diagnosis of solitary VM of the clitoris was made. Magnetic Resonance Imaging showed characteristic features and confirmed the diagnosis and the extent of the VM. This is the first reported case of isolated involvement of the clitoris by VM to be diagnosed preoperatively.